Deep deep sea - Preston-Gannon, Frann (London : Pavilion, 2014)
Underwater animals introduce the numbers one through five.
Keywords: Counting -- Juvenile literature; Marine animals -- Juvenile literature; Board books; Counting; Marine animals; Board books; Counting; Marine animals; Board books for children